Effectiveness of Village Fund Management in Economic and Infrastructure Development - Muh Randy Nurfady; Yati Heryati; Muhtar Mudo (Journal La Bisecoman, 2023)
This study aims to determine the effectiveness of village funds for economic and infrastructure development in Salletto Village. The research method used was a qualitative research method which was taken using the results of interviews conducted with informants namely the Village Head, Village Secretary, Head of General Planning, Hamlet Head and the Community. Data collection methods used are observation, interviews and documentation. The results of the research obtained are that the Salletto Village Economic and Infrastructure Development program has been running quite well when viewed from three indicators of effectiveness starting from the planning indicator where a development program must exist and on time. Implementation indicators where the program planning results from deliberation meetings must be implemented. And the third indicator is monitoring and evaluation where the village government must be able to control the development being carried out so that it can find out whether the development is in accordance with the provisions or not.